1995
DOI: 10.1016/0003-2670(95)00406-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of an adaptive resonance theory based neural network (ART-2a) against other classifiers for rapid sorting of post consumer plastics by remote near-infrared spectroscopic sensing using an InGaAs diode array

Abstract: An Adaptive Resonance Theory Based Artificial Neural Network (ART-2a) has been compared with Multilayer Feedforward Backpropagation of Error Neural Networks (MLF-BP) and with the SIMCA classifier. All three classifiers were applied to achieve rapid sorting of post-consumer plastics by remote near-infrared (NIR) spectroscopy. A new semiconductor diode array detector based on InGaAs technology has been experimentally tested for measuring the NIR spectra. It has been found by a cross validation scheme that MLF-BP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…However, the separation of all 5 clusters is more complex and cannot be shown in a single 3d-plot. It has been shown that the complete separation between all 5 classes can be achieved by neural network classifiers [9].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, the separation of all 5 clusters is more complex and cannot be shown in a single 3d-plot. It has been shown that the complete separation between all 5 classes can be achieved by neural network classifiers [9].…”
Section: Resultsmentioning
confidence: 99%
“…In order to chose the optimal detector material, a detailed preliminary study covering the complete NIR spectral region from 1000 to 2500 nm was carried out [9]. In particular the separation power of different wavelengths was investigated.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…16,[18][19][20][21][22][35][36][37][38][39] 3. EXPERIMENTAL SECTION ART 2-A was applied on a data matrix of 103 aliphatic substituents ( Table 1) described by the hydrophobic constant for aliphatic substituents Fr, H-bonding acceptor (HBA) and donor (HBD) abilities, the molar refractivity (MR), and the inductive parameter F, respectively.…”
Section: Theory Of Art 2-amentioning
confidence: 99%